Message - Al-Shamahy, Prof. Dr. Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2022)
In this article, I will discuss the methods of evaluating the medical and pharmaceutical journal and the obstacles that researchers face in countries similar to the situation in Yemen. To begin with, we should know the Medical Journal; a medical journal is a peer-reviewed scientific journal that conveys medical information to physicians and other health professionals. These journals cover many medical specialties and are sometimes called general medical journals. The first medical journals were general medical journals, created in the late eighteenth century. Specialized medical journals were first introduced in the early twentieth century. It is well known that prestige and rank are one of the attributes of a medical journal and the prestige of an academic journal is established over time, and can reflect many factors, some of which can be quantified but not all. In every academic discipline, there are dominant journals that receive the largest number of applications, and therefore can be selective in their content selection. However, it’s not just the big magazines of excellent quality. The medical journal is evaluated with an impact factor which is a well-established proxy, which measures the number of subsequent articles citing articles already published in the journal. There are other quantitative measures of prestige, such as the total number of citations, how quickly articles are cited, and the average "half-life" of articles. Clarivate Analytics’s Journal Citation Reports, which among other features, calculates the impact factor for academic journals, and derives data for the computation from the Science Citation Index Expanded, and from the Social Science Citation Index (for social science journals). Several other metrics are also used, including SCImago Journal Rank, CiteScore, Eigenfactor, and Altmetrics. After this introduction, I would like to express my opinion on the use of these factors that can be used in establishing the position of the journal, as well as the opportunity to publish medical studies in these journals coming from poor countries, which have little or no support for researchers, and many studies depend on the effort of the researchers themselves only. First: Is the use of current factors that can be used to establish the position of the journal as judges for recent journals? In some disciplines, such as knowledge management/intellectual capital, many academics view this journal rating system as “a major obstacle to tenure, promotion and recognition of achievement and that the pursuit of impact factor accounts is detrimental to science goals, and they signed the San Francisco Declaration on Research Evaluation to limit use it. Second, many of the high rank journals, according to my experience, do not pay any attention to studies coming from poor countries, and if they accept the research for evaluation, the response will be after many months and may be rejected because it was not written well and the research is not reviewed and assisted even if the research topic is valuable. After this description where is UJPR? I would like to testify that our beloved UJPR has made a great effort and steps to change the previous situations, as our esteemed journal is based on the following: Speed ​​of response - Speed ​​of evaluation by the two reviewers - Helping authors with valuable research to rearrange and re-write their research in the correct and appropriate way. These efforts made by the staff of the journal will make our journal in the forefront. In addition, we put more efforts into developing our journal to be in its proper position and to be in SCOPUS and ISI indexed journals. Finally, I conducted a survey among academic medical staffs and medical postgraduate students in our university and the question was “Which journals did you use the most for medical information on Yemen for your research? 80% of them answered UJPR, and I should add that “UJPR has become the most read medical journal in Yemen.”